Inclusión educativa, habilidades diferentes y asperger - Cuzcano Zapata, Abel (2017)
Currently, in the Peruvian school system, policies that effectively support students with special needs, including students with generalized Developmental Disorders, such as children and youth with Asperger Diagnosis, are not fully complied with .